OVER-EXTENSION DAN UNDER-EXTENSION DALAM PEMEROLEHAN SEMANTIS BAHASA INDONESIA ANAK TUNARUNGU - pujiastuti, rahayu; Nurhadi, Taufik (Buana Bastra, 2014)
Abstract Over-extension and under-extension are two of the interesting phenomenas in gaining semantics of deaf children. Both of the phenomenas occur because of the error in giving the semantics feature on one word so that the error distracts the comprehension and word-production meaningfully. This research is a longitudinal qualitative research. The subject of this research is deaf elementary students. The technique of data collection is using observation. It is also supported by feed back, note, and recording. The technique of ata analysis is using transcription, code, and conclusion. Based on the result of data analysis, it can be concluded that (1) over-extension in gaining semantics of bahasa for deaf elementary students in every level of deafness happens in noun, verb, and adjective: (a) the low level of deafness happens in noun, verb, and adjective. (b) the medium level of deafness happens in noun and verb, (c) the high level of deafness happens in noun; (2) under-extension in gaining semantics of deaf elementary students in every level of low, medium, and high happens in noun; (3) The effect of over-extension and under-extension in gaining semantics of deaf elementary students can distract (a) participant, including communicator and communicant (b) the understanding of message, and (c) the ongoing of communication. . Key Words: Over-extension, Under-extension, Effect of Gaining Semantics, and Deaf hildren.